Development of a Conceptual Model to Understand Disease Burden in Patients With Systemic Lupus Erythematosus and Organ Damage - Lynne Broderick; Wen-Hung Chen; Roger A. Levy; April Mitchell Foster; Cindy Umanzor Figueroa; Kerry Gairy; Deven Chauhan (Journal of Health Economics and Outcomes Research)
# Background Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that can lead to irreversible organ damage (OD). Data describing the patient burden of OD, as compared with SLE without OD, are limited.